Concept of Triangle: Examples of Mathematical Abstraction in Two Different Contexts - Nurhasanah, Farida; Kusumah, Yaya S.; Sabandar, Jozua (International Journal on Emerging Mathematics Education, 2017)
Geometry has abstract notions to be learnt so that all those notions cannot be just transferred into studentsâ mind like a bunch of information that should be memorized. Students need to construct those concepts during their learning process. This process of knowledge construction can be considered as an abstraction process. This study aimed to qualitatively compare abstraction process of students who learned the topic of triangle in conventional method and in van Hiele model of teaching aided by Geometersâ sketchpad. Subjects of this study were junior high school students in grade 7. This is a qualitative study with grounded theory design. Data were collected through classroom observation, test, and task-based interview. Results of the study show that theoretical abstraction processes tend to dominate classrom with conventional method of teaching while classroom with van Hiele model of teaching aided by Geometersâ sketchpad accommodated empirical abstraction process of the students.